Evaluation of upper limb function with digitizing tablet-based tests: reliability and discriminative validity in healthy persons and patients with neurological disorders. Issue 8 (10th April 2022) - Schallert, Wolfgang; Fluet, Marie-Christine; Kesselring, Juerg; Kool, Jan
Abstract: Purpose: To evaluate discriminative validity, relative reliability and absolute reliability of four tablet-based tests for the evaluation of upper limb motor function in healthy persons and patients with neurological disorders. Methods: Cross-sectional study in 54 participants: 29 patients with upper limb movement impairment due to a neurological condition recruited from an inpatient rehabilitation centre and 25 healthy persons. Accuracy, speed and path length were analysed for four tablet-based tests: "Spiral drawings, " "Tapping, " "Follow the dot" and "Trace a star." The area under the receiver operating characteristic curve (AUC) was used to evaluate discriminative validity. Relative reliability was analysed with the intra-class correlation coefficient (ICC), and absolute reliability by limits of agreement (LoA) and minimal detectable difference (MDD). Results: All four tests showed excellent discriminative validity for the parameter accuracy (AUC 0.93–0.98). Tapping was the best test for discriminating patients from healthy persons. Test-retest reliability was good for accuracy in all tests (ICC = 0.76–0.88), but poor to moderate for speed and path length (ICC = 0.20–0.69). The MDD varied between 14% and 38%. Performance on the four tablet-based tests was stable between sessions, indicating that there was no learning effect. Conclusion: The parameter accuracy showed excellent discriminative validity and reliability in all four tablet-based tests. Discriminative validity was excellent for all three parameters in the Tapping test. In the other tasks speed showed good to poor reliability, while the reliability of path-length was poor in all tasks. Results were comparable for the dominant and non-dominant hand. Tablet-based tests have the advantage that patients can use them for self-monitoring of upper limb motor function. Implications for rehabilitation: Four tablet-based tests for the assessment of upper limb motor function in patients with upper limb neurological dysfunction were evaluated: "Spiral drawings", "Tapping", "Follow the dot" and "Trace a star". The parameter accuracy in these four tests had excellent discriminative validity and good reliability. Patients can perform the tests independently at home for self-monitoring of progress. This may increase patients' motivation to exercise at home. The results can be sent to physicians, enabling the earlier detection of deterioration, which may require medical attention.